The Effect of a Multi-Nutrients Biscuits Supplemented on Weight Gain of Pregnancy - . Hardinsyah; Dodik Briawan (Media Gizi dan Keluarga, 2000)
The objective of this study was to analyze the effect of multi-nutrients fortified biscuits on weight gain of pregnancy. For this purpose 122 sub samples of 269 total samples of a double blind randomized community trial was selected considering similar age of pregnancy (5 month) at the begining of the intervention. The trial was conducted in 35 villages of Leuwiliang and Cibungbulang District, where infant mortality rate was relatively high. The treatment was randomly assigned into five groups namely basal biscuit which is rich in iron, vitamin A, C and folate (Group-A), basal biscuit fortified with iodine (Group-B), basal biscuit fortified with zinc (Group C) basal biscuit fortified with iodine and zinc (Group-D) and biscuit without any nutrients fortification (Group-E, control group). Five find of formulated biscuits developed from previous study. The biscuits were given 80 a day for three days a week during the second and third treemester of pregnancy. The result showed that the average weight during second and third treemester of pregnancy was 2.3 and 1.5 kg/month respectively. Average total weight gain during intervention was 6.5 kg/month. Among the five group, group D had a significant effect on weight gain of pregnancy. Result from multivariate regression analysis confined that supplementation of biscuit fortified with iron, vitamin A, vitamin C, folate, iodine and zinc (group D) have significant effect on weight gain of pregnancy. Giving this biscuit about 5150 gram during second and third treemester increase 1300 gram of pregnancy weight gain.Keywords: multi-nutriens, weight gain, pregnancy